Early Childhood Studies / An Introduction to the Study of Children's Worlds and Children's Lives - Leeson Caroline; Parker Rees Rod; Savage Jan; William Jenny (Learning Matters, 2010)
Seven new chapters are included in this extensively revised and updated edition, covering topics such as providing enabling environments, families and cultures, and childhoods in other countries. Contributors, Preface, Introduction, What Can Children Do? Sociocultural Factors in Development, Frameworks for Understanding Development, Active Playing and Learning, Developing Communication: Enjoying the Company of Other People, Children's Health and Well-Being: Investing in the Health of the Nation, Working with Children: Extending Opportunities for Participation, Observing Children, Providing an Enabling Environment, Tackling Inequality in the Early Years, Multi-Professional Practice: Developing Empowering Communities, Working With Colleagues, Leadership in Early Childhood Settings, The Benefits of Comparison: Recent Developments in the German Early Years Workforce, Comparing Children's Worlds: Making the Familiar Strange, Adults' Concepts of Childhood, Children's Well-Being in the Developing World, The Research and Policy and Practice Triangle in Early Childhood Education and Care, Researching Practice: Developing Critical Engagement, In Praise of Reflective Practice, Index.